Experience of Czech elite trampolinists and their coaches with lost move syndrome - Novotná, A.; Burešová, I. (Science of Gymnastics Journal, 2024)
This exploratory qualitative study explored the experience of Czech elite trampolinists and their coaches with Lost Move Syndrome (LMS). Six in-depth semi-structured interviews were conducted with three trampolinists (aged from 13 to 20 years) and their coaches (aged from 45 to 46 years with coaching experience ranging from 20 to 28 years). Statements were analysed using interpretative phenomenological analysis. The results contributed to the mapping of this essential but not well-described phenomenon in the literature, showing, in particular, the significant variability in the perceived causes of LMS. Physical manifestations of LMS in individual trampolinists were quite different. Fear and misunderstanding of LMS were common psychological issues in all trampolinists. At the same time, there were significant differences between the experience of LMS by trampolinists and their coaches. The most crucial factor for understanding LMS appears to be personal experience with LMS. The results may be helpful for coaches in practice or sports psychologists to understand trampolinist's experience of LMS further.